Organic phosphorus affects the retention of arsenite and arsenate by goethite. Issue 6 (1st November 2020) - Balint, R.; Celi, L.; Barberis, E.; Prati, M.; Martin, M.
Abstract: The hazardous effects of arsenic are closely linked to its speciation and interaction with different soil minerals, which influence both As mobility and bioavailability. Adsorption onto iron (oxyhydr)oxides is one of the main processes controlling the partitioning of arsenite [As(III)] and arsenate [As(V)] between aqueous and solid phases. Arsenic retention can be affected by changes in soil pH and the presence of competing anions, like phosphate. Although competition with inorganic phosphorus (P) for sorption sites on mineral surfaces has been widely studied, little is known about the interactions with organic P (Po ) compounds, in particular inositol phosphates, even though they may represent a large fraction of total soil P. We quantified the effects of myo ‐inositol hexaphosphate (InsP6) on the adsorption and retention of As(III) and As(V) on goethite as influenced by pH, the order of anion addition, and residence time. The efficiency of InsP6 in displacing adsorbed As(III) decreased with increasing pH values and interaction time, which may be attributed to the increase in bonding strength of the As(III) complexes on the surface of goethite. Adsorption and retention of As(V) by goethite generally decreased with increasing pH, particularly in the presence of InsP6 due to the similar pKa values and the competition for the same binding sites. The addition of InsP6 before, together with, or after adsorption of As(III) and As(V) strongly reduced the amounts of sorbed As, suggesting that the addition of Po –rich matrices to As‐contaminated soils may strongly enhance As mobility.